A Comparison of Sputum Examination for Acid Fast Bacilli by Modified Cold Stain And Ziehl-Neelsen Stain for Screening of Pulmonary Tuberculosis - Tansuphasiri, Unchalee; Kladphuang, Booncherd; Rienthong, Dhanida; Sujirarat, Dusit (Siriraj Medical Journal, 2020)
A comparative study of the conventional Ziehl-Neelsen (ZN) stain and a new modified cold (MC) stain was carried out to evaluate the efficiency of this staining method in sputum examination for acid fast bacilli (AFB). The MC technique was simplified by avoiding the need for heat and combining the stage of counterstaining to overcome the problem aerosolized phenol and the more laborious heating method. Of the 392 sputum samples examined, 84 were positive and 297 were negative on both staining techniques, with an agreement of 97.2%. In comparison with culture as the gold standard for the diagnosis of tuberculosis, the ZN stain exhibited a sensitivity, specificity, positive and negative predictive values and efficiency of 68.9, 97.4, 92.1, 87.8 and 88.8%, respectively. The same values for the MC stain were 70.6, 97.8, 93.3, 88.4 and 89.5%, respectively with no statistically significant differences (P > 0.05) between the 2 methods. The MC stain was also as reliable as the ZN stain in retaining the color of the stained slide after prolonged storage; an agreement with the first reading was 90% after 4 weeks storage and 80% after 16 weeks storage. The staining reagents had a long shelf life; with agreement between both staining methods of 100% at every time of re-stocking aliquots. To apply this new MC stain for future use at the peripheral level of the health care system, we made a survey by using questionnaires sent to 200 hospitals. Most of the respondants also accepted that the MC stain was easier to perform, more comfortable and much less expensive than the ZN stain. Together, these factors make the MC stain suitable for use as a practical and rapid sputum staining test for screening for patients with pulmonary tuberculosis and for assessment of their treatment.